Evaluation of the readiness of hospitals affiliated to Isfahan University of Medical Sciences in unexpected events in 2017 - Fatemeh Rezaei; Zahra Mohebbi-Dehnavi (Journal of Education and Health Promotion, 2019)
INTRODUCTION: The occurrence of natural disasters such as floods, earthquakes, and storms often has devastating effects on human societies and causes heavy casualties on their inhabitants. By destroying the buildings and infrastructure of society, these events impose a wide range of economic and social burdens on societies and countries. Research in the management of incidental accidents improves the ability to respond correctly in the event of accidents. Therefore, this study was conducted to evaluate the readiness of hospitals in unexpected events in 2017. METHODS: This cross-sectional study was conducted in 2017 on 10 selected hospitals affiliated to Isfahan University of Medical Sciences. Data collection with the standard checklist included 137 yes/no questions in 10 areas of emergency, admission, transmission, traffic, communication, security, human resources, management, education, and support. At the end of the study, the data were encoded and entered into the SPSS 22 software and were examined. RESULTS: The results of this study showed that the readiness of hospitals in each of the areas studied was as follows: emergency (79% = good), admission (72.5% = good), transmission (70.4% = good), traffic (58% = moderate), communication (79.6% = Good), security (59.7% = average), human resources (83.6% = very good), management (58% = moderate), education (81% = very good), support (73% = good), and command and management (81.8% = very good). CONCLUSION: Since hospital conditions are completely changed during a crisis, hospital adaptation to new conditions should be based on the projected plans. As a result, everyone should be prepared to take responsibility according to their responsibilities.